Analysis of health literacy level and influencing factors among residents of Anhui province in 2021: a cross-sectional survey - Zhenmin HAN; Zhimin WANG; Jianrong XIE; Yuanrui XIA; Qi TAO; De XU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the current status of health literacy level among residents in Anhui province in 2021, explore related influencing factors, and provide a basis for future health education interventions and health policy formulation. MethodsFrom September to November 2021, a questionnaire survey on health literacy was conducted among 16,668 permanent residents aged 15 - 69 years old in 190 streets (towns) of Anhui province, using a combination of stratified, multi-stage, simple random, and probability proportional to size (PPS) sampling methods. ResultsAfter weighted adjustment, the health literacy level of residents in Anhui province in 2021 was 28.57%. Among the three aspects of health literacy, basic knowledge and concepts accounted for 41.43%, healthy lifestyle and behaviors accounted for 30.16%, and basic skills accounted for 28.21%. Among the six types of health issue literacy, safety and first aid were the highest (61.25%), while basic medical care and infectious disease prevention and control were the lowest (25.71% and 25.43%, respectively). The weak points of health literacy were mainly concentrated in basic skills and basic medical care. Multivariate logistic regression analysis showed that the health literacy level of urban residents was higher than that of rural residents (OR = 1.183, 95%CI: 1.089 - 1.285); compared with the 65 - 69 age group, the health literacy levels of residents aged 15 - 24, 25 - 34, 35 - 44, and 45 - 54 were higher, with OR values of 2.060 (95%CI: 1.510 - 2.810), 2.930 (95%CI: 2.179 - 3.941), 3.343 (95%CI: 2.495 - 4.480), and 2.416 (95%CI: 1.807 - 3.231), respectively; compared with illiterate or semi-literate individuals, the health literacy levels of residents with primary school, junior high school, high school, and college or above education were higher, with OR values of 3.065 (95%CI: 2.102 - 4.468), 7.516 (95%CI = 5.253 - 10.754), 18.302 (95%CI: 12.673 - 26.432), and 49.911 (95%CI: 34.345 - 72.534), respectively; compared with farmers, the health literacy level of civil servants and public institution employees was higher, with an OR value of 1.179 (95%CI: 1.011 - 1.375); compared with an annual family income of < 30 000 yuan, the health literacy levels of residents with an annual income of 30 000 - 100 000 yuan and above 100 000 yuan were higher, with OR values of 1.253 (95%CI: 1.128 - 1.393) and 1.570 (95%CI: 1.403 - 1.758), respectively. ConclusionUrban-rural residency, age, education level, occupation, and annual family income were influencing factors for the health literacy level of residents in Anhui province, with education level being the main influencing factor.